2015
DOI: 10.1149/2.0031509eel
|View full text |Cite
|
Sign up to set email alerts
|

Microvia Filling with Nickel-Tungsten Alloy to Decrease the Coefficient of Thermal Expansion of Electronic Circuit Interconnections

Abstract: A nickel-tungsten alloy plating formula was developed to electrochemically fill the microvias of printed circuit boards and the through-silicon vias (TSVs) of wafers. The plating solution was composed of Ni(SO 3 NH 2 ) 2 , citric acid, sodium citrate, Na 2 WO 4 , chloride ions, and 2-mercapto-5-benzimidazolesulfonic acid. A void-free Ni-W superfilling of a microvia and a TSV were achieved. The tungsten content in the filled alloy varied from 1.5 atom% to 5.5 atom%, depending on the plating temperature. The coe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Another solution to overcome the TEC problems is using low TEC metals and/or alloys to replace the copper. [6][7][8][9] However, the resistivity of these metals and alloys is higher than that of copper, and furthermore, etching is impossible. For example, Y.-T. Lin applied a Ni-W plating formula for filling the TSVs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Another solution to overcome the TEC problems is using low TEC metals and/or alloys to replace the copper. [6][7][8][9] However, the resistivity of these metals and alloys is higher than that of copper, and furthermore, etching is impossible. For example, Y.-T. Lin applied a Ni-W plating formula for filling the TSVs.…”
mentioning
confidence: 99%
“…The Ni-W alloy showed a lower TEC value (approximately 14 × 10 −6 (1/ • C) as compared to the TEC of copper. These Ni-W filled TSVs exhibited good thermal stabilities after being annealed at 500 • C for 4 h. 6 M.-H. Roh tried to suppress the extrusion of copper out of TSV by using Cu-W alloys. The results showed that the thermal expansion coefficient of Cu-7.6%wt W was only 10.8 × 10 −6 (1/ • C).…”
mentioning
confidence: 99%
“…Both electroanalytical measurements and the geometry of feature filling indicate the S-NDR mechanism. This paper uses polyethyleneimine (PEI) for filling of much larger TSVs because it enables localized, superconformal filling of TSVs (9) and microcracks (13,14) with ferrous metals including Ni and Ni-alloys (15). It shows a subset of experimental results from a study that follows the path of the Ni study, including electroanalytical measurements and Co deposition in TSVs using a CoSO 4 + CoCl 2 + H 3 BO 3 electrolyte with the branched PEI suppressor.…”
Section: Introductionmentioning
confidence: 99%
“…In larger features in particular, suppressor containing electrolytes that exhibit suppressor induced critical behavior (i.e., S-shaped Negative Differential Resistance, S-NDR) have been used to obtain bottom-up Cu filling of TSVs (1)(2)(3)(4). Suppressor-containing electrolytes exhibiting S-NDR have also been used to obtain localized, superconformal filling of features with Ni and Ni alloys (5)(6)(7)(8), Au (9) and Zn (10). Two types of filling evolution are observed, with complete bottom-up deposition and TSV filling achieved at a single potential with Cu (1) that contrasts with a passive-active transition at a distance down the filling feature, the position dictated by the applied potential and the suppressor concentration, exhibited by Au (9) and Ni (8).…”
Section: Introductionmentioning
confidence: 99%